Resistance exercise performed with repetitions until failure affects nocturnal blood pressure decreases in hypertensive women - Correia, Marilia de Almeida (2015)
Studies have shown that resistance exercise reduces 24-hour blood pressure to levels below resting values, although this is not a universal finding. The number of repetitions has been shown to influence this response. Thus, the aim of the study was to analyze the effects of resistance exercise performed until failure (UF) on 24-hour blood pressure in hypertensive women. Thirteen hypertensive women underwent three experimental sessions in random order: UF, resistance exercise with repetitions before concentric failure (BF) and control (C). Prior to and up to 24 hours after the sessions, cardiovascular variables, as well as the nocturnal fall in blood pressure, the morning surge, and the presence or absence of a blood pressure dip pattern were established using an ambulatory blood pressure monitor. In both wakefulness and sleep there was no significant difference among the three groups. However, after UF and C fewer patients presented a dip in blood pressure (46% and 38%, respectively) compared BF (77%), p=0.047. In conclusion, the UF attenuated blood pressure dips at night in hypertensive patients.